Foods of Colombia - Sheen, Barbara; Gale Group (Detroit KidHaven Press, 2012)
Explores the foods, cooking traditions, customs, eating habits, and food sources of Colombia. Topics include favorite dishes, snacks and sweets, traditional holiday meals, and the preparations and traditions associated with these foods.
Ch 1. Land of plenty -- ch 2. Recipes have regional twists -- ch 3. A snack before supper -- ch 4. It's party time.
Electronic reproduction.
Keywords: Cooking, Colombian -- Juvenile literature; Food -- Colombia -- Juvenile literature; Colombia -- Social life and customs; Electronic books